FOREIGN MEDIA’S REACTION OVER POLITICAL DYNASTY IN INDONESIA - Nauvallina, Fauzia Hasna; Khristianto (Lire Journal (Journal of Linguistics and Literature), 2025)
This study aims to determine the perspectives of foreign media over the issue of political dynasty issue at the last presidential election in Indonesia. This study employed a qualitative approach. The data used is news from South China Morning Post titled “Nepotism May Win Indonesia’s 2024 Election”. To analyze the political text, two theories were applied. They are appraisal theory (Martin & White, 2005) focusing on the affect as part of the attitude aspect, and the ideological square concept (van Dijk, 2006). Based on the analysis, the findings showed that the reporter felt anxious (insecurity as a part of affect) about Joko Widodo leading through political dynasties, because this could hurt Indonesia. To show his negative view, the reporter emphasizes negative points about "them" (Jokowi and his party). In contrary, The post editor felt secure (security as a part of affect) in Jokowi, despite political dynasties based on his past success and popularity. However, he still emphasized the negative sides of political dynasties, even though he liked Jokowi. Meanwhile, the Indonesian analyst felt fear (disinclination as a part of affect). He worried that political dynasties would damage trust and may cause a long-term chaos. Thus, he emphasized the negative of Joko's strategies, not his qualities.